2020 IEEE European Symposium on Security and Privacy Workshops (EuroS&PW) 2020
DOI: 10.1109/eurospw51379.2020.00039
|View full text |Cite
|
Sign up to set email alerts
|

"Security should be there by default": Investigating how journalists perceive and respond to risks from the Internet of Things

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Even an article discussing the implications of "tech tools" used by a technology and media journalist did not mention IoT devices at all, but instead solely focused on smartphone applications and the consequences of targeted advertising [29]. Similarly, our pilot study found that news organisations' cyber protection policies and strategies currently do not incorporate the IoT [5]. Based on this, our categories and threat titles are followed by hypotheticals that describe possible consequences of such threats for the press.…”
Section: Iot and Journalism Threat Modellingmentioning
confidence: 90%
See 4 more Smart Citations
“…Even an article discussing the implications of "tech tools" used by a technology and media journalist did not mention IoT devices at all, but instead solely focused on smartphone applications and the consequences of targeted advertising [29]. Similarly, our pilot study found that news organisations' cyber protection policies and strategies currently do not incorporate the IoT [5]. Based on this, our categories and threat titles are followed by hypotheticals that describe possible consequences of such threats for the press.…”
Section: Iot and Journalism Threat Modellingmentioning
confidence: 90%
“…Two research questions were developed from previous research on this topic, which demonstrated that journalists are not cognisant of consumer IoT threats and do not currently have access to relevant educational resources [5]. These questions are: (1) "What are the distinctive and novel threats to journalism from the consumer IoT?"…”
Section: Research Questionsmentioning
confidence: 99%
See 3 more Smart Citations